A new species of Brethesiella (Hymenoptera: Encyrtidae) from California, USA, a parasitoid of Steatococcus tabernicolus (Hemiptera: Margarodidae) - Trjapitzin, Vladimir A.; Triapitsyn, Serguei V. (Zootaxa, 2006)
A new species of the encyrtid wasp genus Brethesiella Porter, 1920 is described from the Mojave Desert in California, USA. The type series of B. mojave sp. n. was reared from the margarodid scale Steatococcus tabernicolus Ferris on creosote bush, Larrea tridentata. The genus Aztecencyrtus Timberlake, 1926 is synonymized under Brethesiella and its two described species are transferred to the latter as B. flava (Timberlake, 1926) comb. n. and B. iceryae (Howard, 1892) comb. n. A brief review of the encyrtid parasitoids of Margarodidae, a diagnosis of Brethesiella, and an annotated key to its six described species with known females in the New World are provided.